1996
DOI: 10.2307/3236287
|View full text |Cite
|
Sign up to set email alerts
|

In situregeneration ofPinus strobusandP. resinosain the Great Lakes forest communities of Canada

Abstract: Abstract. Two extensive forest vegetation survey datasets are explored, using ordination and classification, for evidence of in situ regeneration by Pinus strobus (Eastern white pine) and P. resinosa (Red pine). Ordination of tree species contributions to total basal area in 320 upland northern hardwood‐ conifer stands produced distinct stand groups for P.banksiana, P. resinosa, P. strobus and mesic hardwoods in an ascending sequence along the first axis. Quercus rubra (red oak), Q. alba (white oak) and toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 22 publications
(23 reference statements)
1
31
0
2
Order By: Relevance
“…This "storage effect" is embodied by the dynamics of temperate conifer-angiosperm mixtures. Long canopy residence times enable conifers to coexist with angiosperms in many temperate forests, despite infrequent recruitment (Read and Hill, 1988;Lusk and Ogden, 1992;Carleton et al, 1996;Lusk and Smith, 1998). Data reviews have confirmed that conifers are appreciably longer-lived, on average, than angiosperm canopy trees in temperate forests of both Northern and Southern hemispheres (Loehle, 1988;Enright and Ogden, 1995).…”
Section: Leaf Traitsmentioning
confidence: 93%
“…This "storage effect" is embodied by the dynamics of temperate conifer-angiosperm mixtures. Long canopy residence times enable conifers to coexist with angiosperms in many temperate forests, despite infrequent recruitment (Read and Hill, 1988;Lusk and Ogden, 1992;Carleton et al, 1996;Lusk and Smith, 1998). Data reviews have confirmed that conifers are appreciably longer-lived, on average, than angiosperm canopy trees in temperate forests of both Northern and Southern hemispheres (Loehle, 1988;Enright and Ogden, 1995).…”
Section: Leaf Traitsmentioning
confidence: 93%
“…In the Great Lakes-St. Lawrence forest, red pine (Pinus resinosa Sol. ex Aiton (Pinaceae)) and white pine (Pinus strobus L. (Pinaceae)) are the two dominant tree species over shallow soils of the Canadian Shield and are often codominant in Ontario at latitudes between 45 and 46°N (Carleton et al 1996). These two species, however, diVer greatly in their total abundance and associations with other species at diVerent latitudes.…”
Section: Study Site and Study Speciesmentioning
confidence: 98%
“…Mixed tol-erant hardwood -white pine stands are often managed under single-tree selection cutting but this method is not necessarily suitable for white pine regeneration, a mid-tolerant species (Lessard et al 1999). In mixedwood forests of Canada and northeastern United States, white pine advance regeneration is often present in very small gaps or under partial canopies, but this species is often suppressed by other vegetation and does not reach later developmental stages (saplings and poles) (Leak et al 1995, Carleton et al 1996. In natural tolerant hardwood stands, it was hypothesized that white pine could regenerate in large canopy openings or in low-density stands.…”
Section: Introductionmentioning
confidence: 99%